Parallel versus perpendicular plots - Raja Yusof, R.J.; Zainuddin, R.; Mohd Yusoff, Z. (2010)
A comparison study between parallel and perpendicular (scatter plot) plot visualization techniques are addressed. Comparison discussion focuses on the disadvantage and advantages of the two techniques and a GOMS analysis of the related tasks based on a system called the PaCQ interface.